Convective Heat Transfer Analysis on Prandtl Fluid Model with Peristalsis - A. Alsaedi; Naheed Batool; H. Yasmin; T. Hayat (Applied Bionics and Biomechanics)
The effects of magnetohydrodynamic (MHD) on peristaltic transport of Prandtl fluid in a symmetric channel have been studied under the assumptions of long wave length and low-Reynolds number. Channel walls are considered compliant in nature. Series solutions of axial velocity, stream function and temperature are given by using regular perturbation technique for small values of Prandtl fluid parameter. The effects of physical parameters on the velocity, streamlines and temperature are examined by plotting graphs.